Diamond Surfaces with Clickable Antifouling Polymer Coating for Microarray‐Based Biosensing. Issue 33 (10th October 2022) - Kumar, Ravi; Yang, Bingquan; Barton, Jan; Stejfova, Miroslava; Schäfer, Andreas; Koenig, Meike; Knittel, Peter; Cigler, Petr; Hirtz, Michael
Abstract: Diamond enables the construction of various (bio)sensors, including those with quantum‐based detection. However, bare diamond interfaces are susceptible to unspecific adhesion of proteins and other macromolecules from biological media or complex samples. This impairs selectivity in biosensing, leads to low signal‐to‐noise ratio in fluorescence‐based applications, and introduces the need for blocking steps in incubation protocols. Here, a stable, protein‐repellent, and clickable reactive polymer coating is introduced, abolishing unspecific protein adhesion while concurrently enabling covalent immobilization of functional compounds as recognition elements. The polymer coating has two segments, an antifouling poly( N ‐(2‐hydroxypropyl) methacrylamide) and an alkyne‐terminated poly(propargyl methacrylamide) providing the click functionality. The antifouling properties and click‐reactivity of the polymers are demonstrated by selective protein binding assays on micropatterns written by microchannel cantilever spotting (µCS). The assays demonstrated the successful functionalization of both diamond and glass surfaces and the excellent antifouling properties of the polymer coating. The coating procedure is compatible with oxidized diamond surfaces thus well‐suitable for diamond‐based quantum technology. The results can directly impact applications of diamond materials in optically detected quantum sensing or fluorescence sensing in general. The polymer functionalization can also be used for any case where highly specific interaction with low fouling is desired. Abstract : While diamond is of high interest for biosensing applications due to favorable material properties, a major drawback is the high susceptibility of bare diamond surfaces for unspecific protein adhesion. Here, a two‐segment polymer coating is demonstrated to efficiently block diamond surfaces with a covalently bound thin anti‐fouling film that remains active for the clicking of additional functional elements.